2020
DOI: 10.19053/01211048.9656
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the presence tutorials in the academic performance of the administration students of a university of the north of Mexico

Abstract: The purpose of the study was to identify the effect of the face-to-face tutoring program of undergraduate students in Administration on academic performance, as well as its level of student satisfaction with the program. The research questions were: (a) what are the aspects of the institutional tutoring program that impact on the academic performance of the students? (B) What is the satisfaction stage from the tutored about the tutoring institutional program attended? and (c) what effect does the institutional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…Es así como este padecimiento se hace presente en distintas universidades donde se encuentran cifras alarmantes. Entre las principales características de depresión en estudiantes universitarios se destaca la somnolencia, incapacidad para relajarse, sentimiento de tristeza, problemas de concentración y desgano al realizar actividades académicas (Armenta et al, 2020;Cóndor et al, 2021), esto se ve evidenciado en cifras de sintomatología de depresión; con el 31,2% en estudiantes que cursan el ciclo de formación profesional y el 23,8% en el ciclo básico de una Universidad Colombiana (Lopez et al, 2022;Manangón et al, 2020;Palacios et al, 2022).…”
Section: Resultsunclassified
“…Es así como este padecimiento se hace presente en distintas universidades donde se encuentran cifras alarmantes. Entre las principales características de depresión en estudiantes universitarios se destaca la somnolencia, incapacidad para relajarse, sentimiento de tristeza, problemas de concentración y desgano al realizar actividades académicas (Armenta et al, 2020;Cóndor et al, 2021), esto se ve evidenciado en cifras de sintomatología de depresión; con el 31,2% en estudiantes que cursan el ciclo de formación profesional y el 23,8% en el ciclo básico de una Universidad Colombiana (Lopez et al, 2022;Manangón et al, 2020;Palacios et al, 2022).…”
Section: Resultsunclassified
“…Moreover, research results of Ullah [27] and Armenta [28] concluded that aiding students' needs enhanced the academic achievement of students in the experimental group significantly, hence, it was an effective method of instruction for teaching at secondary level. They further suggested other teaching methodologies must be incorporated in the teaching and learning process, and it may be given due consideration in all teacher education practices.…”
Section: Test Significance On Students' Performance On Sol Aol and MDLmentioning
confidence: 96%
“…Moreover, the research results of Ullah [30] and Armenta [31] revealed that providing assistance like remedial classes to students have posted valuable and significant improvements on students' achievements and performance. Therefore, initiatives like this can be of great help to struggling learners or students.…”
Section: Level Of Performance In Mathematicsmentioning
confidence: 99%